Paul Muldoon and the Context of Postmodernity - Grgas, Stipe (1999)
The author gives a reading of the work of the Irish poet P. Muldoon within the context of the postmodern society. The analysis attempts to show the traces of postmodernity in Muldoon's texts and to delineate the position of Muldoon's poetry in relation to other Irish poets.
Projekt MZOS
ENG